A constituição da profissionalidade docente e a inovação pedagógica na educação básica - Salami, Marcelo Cesar (Universidade do Vale do Rio dos Sinos, 2013)
The research, case study, focuses on the constitution of the professionalism of teachers who perform innovative practices in La Salle College Esteio. Sought to examine how the trajectories personal, academic (training) and professional of teachers leverage teaching practices from the perspective of innovation. Wanted to identify indicators of educational innovation from teachers' reports, relating them to the indicators already built on research with professors, checking which recurred in both contexts. Sought to understand, yet which indicators more present in the context of basic education and identify, from the design of the research subjects, elements of initial and ongoing training who are essential to promote quality education. In the study used a qualitative methodology that allowed us to understand the teaching professionalism from the context of their teaching practices, their perceptions and representations of the same. Data collection involved two perspectives. At first, to get callers to the survey, a questionnaire was used, enabling who teachers did indication of colleagues who considered innovative in their teaching practices. In the second step, the six teachers nominated by their peers, participated in the case study, when the data collection made use of semistructured interview. Data analysis was performed from Bardin, following the categories already built in the studies of Cunha and Lucarelli. The main research findings indicate that: a) the trajectories personal, academic (training) and professional are elements what constitutes teacher professionalism and devices that potentiate the pedagogical innovation; b) teachers of the study demonstrate concern for the proper development of their students, revealing that their professionalism assume the perspective of an an ethical and social commitment; c) the ordering of pedagogical innovation indicators reveals the conception of teaching and learning which regulates and guides the practice of teachers participating in this study. Somehow these indicators take on a feature of an epistemological-pedagogical dialogues permanently with the administrative, organizational, economic and psychosocial obstacle of the educational institution; d) continuing education can no longer be understood as a personal choice or option, for now to be an "imperative", dictated mainly by the environment of rapidly changing socio-cultural and technological; e) the classroom is an absolute laboratory for innovative teaching practices, where they germinate formative experiences both for the students and for teachers; f ) the students themselves, in some circumstances, become a source of knowledge for teachers. It is necessary, in the pedagogical process of emancipation, consider the value of listening to students; g) there is an enchantment and disenchantment by the teaching profession determined by the working conditions and institutional support; and h) some teachers do not recognize their innovative character in school space. The recognition from colleagues who admire and perceive your work.
Keywords: Profissionalidade docente; Inovação pedagógica; Formação docente; Educação básica; Teacher professionalism; Pedagogical innovation; Teacher training; Basic education; ACCNPQ::Ciências Humanas::Educação